UPAYA NGOS DI UNI EROPA MENANGANI HONOUR KILLING. STUDI KASUS : NEGARA JERMAN - Dinda Fenti Gigih Ceria; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study is a contemporary study that discusses the efforts of Non-Governmental Organizations in the European Union in dealing with honor killings in their country especially in Germany. Honour killing is a phenomenon that occurs in the patriarchal family where a group of men killing their female children or women in the family who is deemed to have brought shame and ruin the family honor. Forms of honor killing is varied, either by being killed, burnt or tortured to death. This action is considered to restore the value of the honor that has been broken, and to strengthen the role of the man in control of his family. Because in the family and the woman is not entitled to refuse anything. This act have occurred in various parts of the world, including European Union. Where the perpetrators of honor killing is mostly derived from groups of migrants that came from Turkey, Pakistan and Kurdish. Type of this research is descriptive analysis. The writer try to describe and explain about NGOs‟s role in solving honour killing which occurred in all over European Union‟s country.The phenomenon of honour killing was motivated by a variety motives, such as refusing arranged marriages, asking for divorce, and being too western, and demands her freedom. Overall, this research is about how NGOs can reduce an honour killing act and keep the security for women, especially for women‟s right.Keywords: Honour killing, NGOs, Women, Violence.